The Influence of Tourist Attraction, Accessibility, and Facilities on Tourists' Revisit Intention at Kasap Beach, Pacitan Regency - Aryani, Novita; Adiyani, Rini; Darmaningrum, Kurniawati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the influence of (1) Tourist Attraction, (2) Accessibility, and (3) Facilities on the Intention of Tourists to Revisit Kasap Beach, Pacitan Regency, both partially and simultaneously. Methodology: This type of research is quantitative descriptive, where data is collected by dividing questionnaires of 100 respondents who have visited the Kasap Beach Tourism object, Pacitan Regency. Data analysis was carried out using multiple linear regression and using SPSS version 25 software. Main Findings: The results of this study show that Tourist Attraction partially has an impact on Intention to Revisit by 28%, Accessibility has an impact of 37.4%, and Facilities by 26.3%. Simultaneously, these three variables had a significant impact on the intention to revisit, with a significance value of 0.000 < 0.05. Novelty/Originality of this study: This research makes a new contribution by analyzing the influence of tourist attractions, accessibility, and facilities on the intention to revisit partially and simultaneously, which has not been widely studied in the context of Kasap Beach. These findings broaden our understanding of the determinants of tourist loyalty and provide a scientific basis for the development of data-driven tourism strategies in similar destinations.